PENGARUH PEMAHAMAN, TRANSPARANSI DAN PERAN PEMERINTAH TERHADAP MOTIVASI DAN KEPUTUSAN MEMBAYAR ZAKAT PADA BAZNAS KOTA BINJAI - Asminar Asminar (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2017)
This study aims to determine the direct and indirect influence of understanding, transparency and the role of government against the motivation and decision to pay zakat at Baznas Kota Binjai. The research method used quantitative approach of path analysis with multiple linear regression model with SPSS version 16 program. The result of research shows that the coefficient of determination of structural model 1 is 60.6% understanding, transparency and role of government to motivation. While the structural model 2 is 94.8% understanding, transparency, role of government and motivation influence Muzaki decision. Simultaneously on structural model 1 shows understanding, transparency, the role of government toward motivation significantly influences. While on structural model 2 shows understanding, transparency, role of government and motivation to decision muzaki have significant effect. The significance test of indirect influence indicates the indirect influence of understanding, transparency, the role of government against the decision to pay zakat through motivation significantly.